2008
DOI: 10.1007/s12253-008-9020-5
|View full text |Cite
|
Sign up to set email alerts
|

EGFR Inhibitor Enhances Cisplatin Sensitivity of Oral Squamous Cell Carcinoma Cell Lines

Abstract: Epidermal growth factor receptor (EGFR) is involved in multiple aspects of cancer cell biology. EGFR has already been identified as an important target for cancer therapy, with various kinds of EGFR inhibitors currently used in treatment of several human cancers. Recently, EGFR and its downstream signaling pathways were identified as being associated with cisplatin sensitivity. In addition, EGFR inhibitors have shown significant promise for patients who failed cisplatin-based therapy. In this study, we investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
43
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 26 publications
5
43
0
Order By: Relevance
“…These signal transduction pathways activated by pEGFR are important in cell differentiation, proliferation, migration, adhesion and apoptosis (15). It has been reported that the chemoresistance of several types of tumors including bladder cancer are associated with EGFR and pEGFR overexpression (16,17). These findings indicated that LRIG1 may enhance the sensitivity of cancer cells to chemotherapeutic agents.…”
Section: Introductionmentioning
confidence: 99%
“…These signal transduction pathways activated by pEGFR are important in cell differentiation, proliferation, migration, adhesion and apoptosis (15). It has been reported that the chemoresistance of several types of tumors including bladder cancer are associated with EGFR and pEGFR overexpression (16,17). These findings indicated that LRIG1 may enhance the sensitivity of cancer cells to chemotherapeutic agents.…”
Section: Introductionmentioning
confidence: 99%
“…A panel of four cisplatin-resistant neuroblastoma cell lines have also been shown to have increased EGFR and pEGFR protein expression and be more sensitive to treatment with novel EGFR-targeted agents than their cisplatin-sensitive counterparts (Michaelis et al, 2008). Similar results were seen in two cisplatin-resistant oral carcinoma cell lines, increased EGFR and pEGFR and sensitivity to the novel EGFR inhibitor AG1478 (Hiraishi et al, 2008). Therefore, treatment with platinum and the development of platinum resistance may cause EGFR dysfunction by altering the protein expression and activity of components of the EGFR pathway in a subpopulation of relapsed cancer patients.…”
Section: Introductionmentioning
confidence: 61%
“…[24] Lapatinib inhibits the tyrosine kinase activity associated with EGFR and human EGFR 2 (HER 2). [25] A pilot phase II study was conducted by Pfister et al to generate pilot data for a novel paradigm for combined-modality therapy through the integration of a biologically active, targeted agent with an established concurrent chemoradiotherapy program.…”
Section: Combination Therapy With Egfr Inhibitorsmentioning
confidence: 99%